Just boundaries for demoicrats - Nicolaidis, K; Viehoff, J (Taylor and Francis, 2017)
This article asks what features should characterise the boundaries between the EU and the outside world from the standpoint of demoicracy. Section one summarises the normative core of that view and grounds it in the values of autonomy, equal recognition and non-domination. Section two categorises the issues that arise for the demoicrat when it comes to the consequences of political borders. We demonstrate – through the example of intra-demoicracy border crossing – why demoicrats will seek to follow the three desiderata of procedural fairness, just outcomes, and overall consistency in designing political solutions. Section three defends a set of principles that would ideally govern large-scale arrival of refugees. Section four addresses questions of non-ideal theory, reflecting on how demoïcratic theorists should think about current EU policies. Though we do not offer a comprehensive solution to the tensions we identify, the conclusion offers some proposals of how demoicrats may alleviate them.